2023
DOI: 10.3390/jpm13030429
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Injections of Platelet-Rich Plasma Versus Hyaluronic Acid for Knee Osteoarthritis: A Systematic Review and Meta-Analysis of Current Evidence in Randomized Controlled Trials

Abstract: In recent years, various clinical trials have focused on treating knee osteoarthritis (KOA) with multiple injections of platelet-rich plasma (PRP). However, compared with the multiple hyaluronic acid (m-HA) injections, the clinical efficacy of multiple PRP (m-PRP) injections for KOA still remains controversial among these studies. Therefore,we aimed to compare the clinical effectiveness of m-PRP injections with m-HA injections in the treatment of KOA in this systematic review. Relevant clinical trials were sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 64 publications
0
1
0
Order By: Relevance
“…PRP is a concentrated solution of platelets that is rich in growth factors, showing the ability to facilitate angiogenesis, neuroprotection, neural regeneration, regulation of inflammation with broad therapeutic applications [17,[32][33][34][35][36][37][38][39][40][41][42]. Comparative studies have shown the clinical advantages of PRP injection for patients with incomplete RC tears.…”
Section: Discussionmentioning
confidence: 99%
“…PRP is a concentrated solution of platelets that is rich in growth factors, showing the ability to facilitate angiogenesis, neuroprotection, neural regeneration, regulation of inflammation with broad therapeutic applications [17,[32][33][34][35][36][37][38][39][40][41][42]. Comparative studies have shown the clinical advantages of PRP injection for patients with incomplete RC tears.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis of 463 patients also found that patients who received the m-PRP injections had significantly lower scores on VAS and WOMAC than patients who received the m-HA injections. A RCT involving 162 participants revealed that administering multiple PRP injections is more efficacious than single injections and hyaluronic acid in treating early osteoarthritis in the knees [25,30,31].…”
Section: Discussionmentioning
confidence: 99%
“…PRP solution contains a concentration of platelets 3 to 8 times higher than that of normal blood, which provides several theoretical advantages for tissue regeneration during various pathological conditions 30 . Recent clinical studies have demonstrated the efficacy of PRP infusion in treating chronic diabetic ulcers 31 , osteoarthritis of the knee joint 32 , plantar fasciitis 33 , and even military drill injuries 4 . Moreover, since PRP solution also contains white blood cells in sufficient quantity, it is believed to enhance the body's defense against local inflammation and its attempt to eliminate local pathogenic microorganisms 34 .…”
Section: Discussionmentioning
confidence: 99%
“…These components give PRP important biological properties that can aid in tissue repair and regeneration, and improve local microcirculation in the area where it is injected 5 . As a minimally invasive method, in recent years it has found important therapeutic applications in various pathological conditions that involve multiple medical specialties, such as orthopaedics 6 , rheumatology 7 , plastic surgery 8 and dermatology 9 .…”
Section: Jrpmsmentioning
confidence: 99%